Risk Factors Associated with Low Apgar Scores in Pregnancies Complicated by Severe Preeclampsia: A Case–Control Study - Yunxia Wang; Bihong Cui; Jiuju Zhou; Shuang Yue; Chun Wang; Yongzhong Gu; Jinlai Meng (Clinical and Experimental Obstetrics & Gynecology)
Background: Neonates born to women with severe preeclampsia (PE) exhibited lower Apgar scores. The purpose of this study was to evaluate the association between low Apgar scores and maternal, prenatal, and intrapartum variables in patients with severe PE. Methods: A retrospective case–control study was conducted in a public teaching hospital from January 2016 to June 2022. Cases included patients with severe PE and an Apgar score below 7 at 1 or 5 minutes, while controls had severe PE with an Apgar score of 7 or higher. A total of 125 cases and 303 controls were included. Fisher's exact test, logistic regression and receiver operating characteristic (ROC) analysis were used as appropriated. Results: 22 potential risk factors were assessed, of which 12 were significantly associated with changes in outcome. Multivariate analysis identified gestational age at delivery (GAD) (odds ratio [OR], 0.570; 95% confidence interval [CI], 0.420–0.774; p < 0.001), intravenous anesthesia (OR, 12.889; 95% CI, 3.820–43.486; p < 0.001) and PE onset weeks (OR, 0.937; 95% CI, 0.879–0.999; p = 0.047) as independent risk factors for low Apgar scores in neonates with severe PE. The accuracy of predicting low Apgar scores in newborns of PE patients was high based on GAD (area under the curve [AUC], 0.868; 95% CI, 0.832–0.905; p < 0.001) and PE onset weeks (AUC, 0.785; 95% CI, 0.741–0.828; p < 0.001). Conclusion: The GAD (<30.5 weeks) and PE onset weeks (<28.5 weeks) are identified as risk factors for low Apgar scores in newborns of patients with severe PE, and general anesthesia is suggested to be avoided during delivery.